PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS LEARNING CYCLE 5E PADA SUB MATERI KONSEP MOL DAN PERHITUNGAN KIMIA KELAS X MIA SMA NEGERI 1 MANDOR - Eka Nurmala; Fitriani Fitriani; Dedeh Kurniasih (Universitas Muhammadiyah Pontianak, 2019)
This study is motivated by the student’s problems in comprehending the Mol concept and Chemical Calculations. It is aimed at producing the student’s worksheet based on Learning Cycle 5E at the Mole Concept and Chemical Calculations for the tenth grade students of Science and Math class of SMA Negeri 1 Mandor. Using Research and Develoment (R&D) model of 4D, this study focused on three stages of the model; Define, Design, and Develop. The sample of this study were 21 students of SMA Negeri 1 Mandor. The data collection techniques were an interview, observation, measurement, and indirect communication. To complete the data, this study employed validation sheet, student’s and teacher’s questionnaires, and the result of pre-and post-tests as the instruments. The study revealed that the validation criteria validated by the experts was strongly valid (99,65%), and the media criteria was also strongly valid (95,83%). The results of the practicality of the try small-scale out were 81,12%, and the main try out were 95,83%. In other words, both small-scale and main try out were considered practical. Additionally, the N-gain showed the effectiveness criteria of the student’s worksheet based on Learning Cycle 5E at the Mole Concept and Chemical Calculations on the main try out by 0,84% (highly satisfactory). In conclusion, the student’s worksheet based on Learning Cycle 5E at the Mole Concept and Chemical Calculations is valid and suitable to be used as the learning materials for the tenth grade students of science and math class of SMA Negeri 1 Mandor.